The Introduced Fanworm, Sabella spallanzanii, Alters Soft Sediment Macrofauna and Bacterial Communities - Atalah, Javier; Floerl, Oliver; Pochon, Xavier; Townsend, Michael; Tait, Leigh; Lohrer, Andrew M. (Frontiers in Ecology and Evolution, 2019)
The Mediterranean fanworm, Sabella spallanzanii, is listed as an introduced and established “unwanted species” in New Zealand, subject to nationwide targeted surveillance in port, marina, urban and natural environments. Sabella spallanzanii has the potential to change soft-sediment benthic habitats due to the physical presence of the fanworm's tube and associated biological activities, particularly suspension feeding and bio-deposition. A 6-month field experiment was conducted to investigate the impacts of S. spallanzanii on the structure and diversity of existing communities within invaded soft-sediment habitats. Macrofaunal communities were assessed using traditional sampling and identification via microscopy, while microbial and eukaryotic communities were characterized using metabarcoding of 16S and 18S ribosomal genes, respectively. Live and mimic S. spallanzanii were transplanted at different densities (10–50 individuals per m2) into experimental plots with existing assemblages, to test for potential biological and/or physical effects on benthic communities. Analyses revealed significant differences in macrofaunal, eukaryote, and bacterial assemblages in the presence of live S. spallanzanii and mimics, underpinned by changes in the relative abundance of several taxa, indicating that these effects are brought about by biological and physical functions. The presence of S. spallanzanii did not alter total abundance and taxa richness of benthic assemblages but resulted in compositional differences. We found no effect of live or mimic worm density on the structure and diversity of the studied communities. Changes in the structure of native benthic communities, as indicated by this study, can potentially impact functioning of soft-sediment habitats, through alterations to nutrient cycling, bioturbation and benthic-pelagic coupling. Quantitative measurements of impacts are crucial to understand the trajectory of marine invasions, their roles in re-structuring communities, and to guide management efforts.